A multiregional survey of nickel in outdoor air particulate matter in China: Implication for human exposure. (May 2018) - Li, Han; Wan, Yanjian; Chen, Xiao; Cheng, Lu; Yang, Xueyu; Xia, Wei; Xu, Shunqing; Zhang, Hongling
Abstract: Nickel is a widespread environmental contaminant, and it is toxic to humans in certain forms at high doses. Despite this, nationwide data on nickel in outdoor air particulate matter and human exposure to nickel through inhalation in China are limited. In the present study, 662 outdoor air samples from seven representative provinces such as Shanghai, Hubei, Hunan, Hebei, Guangdong, Yunnan, and Shanxi were collected between March 2013 and February 2014 and analyzed by inductively coupled plasma mass spectrometry. The concentrations of nickel in the air were in the range of 2.1–80.9 ng/m 3 (geometric mean: 14.4 ng/m 3 ). In most areas, the concentrations of nickel were higher in winter and spring than those measured in summer and autumn. The daily intake (median) of nickel through inhalation of air particulate matter was estimated. Although the nickel concentrations in some air samples were high, inhalation of the air particulate matter accounted for a minor part of the total nickel intake; however, the adverse effects of human exposure to nickel through inhalation and its potential sources require more attention, particularly in Shanghai. This is a multiregional survey of nickel in outdoor air particulate matter in China. Graphical abstract: Image 1 Highlights: We analyzed the Ni levels of 662 outdoor air samples from 7 provinces in China. The concentrations of Ni in air were in the range of 2.1–80.9 ng/m 3 . In most areas, the Ni concentrations were higher in winter and spring. Estimated daily intake doses of Ni through inhalation were calculated. This is a multiregional survey of Ni in outdoor air particulate matter in China.